Developing Halal Tourism: The Case of Bongo Village, Gorontalo, Indonesia - Izudin, Ahmad (The international journal of religious tourism and pilgrimage, 2022)
Religious tourism is one of the oldest forms of tourism in Indonesia’s Gorontalo Province, which is rapidly growing to be a halal tourism destination. Such a tourism concept has created new products in the industry. However, limited research has curtailed the potential of religious tourism in Gorontalo. As a contribution to the research on religious tourism, this paper explores of religious tourism as a new method to develop Indonesia’s tourism industry. The study uses qualitative methods to review the potential of religious tourism in Gorontalo. The case study was undertaken with in-depth interviews, documentation, and observation to examine the benefits of religious tourism in Bongo, based on an evaluation of religious tourism and halal tourism. The findings show that this religious tourist village contributes to this developing country. Hence, travel and tourism have grown along with various forms of religious tourism (linked with biodiversity, landscape appreciation, and socio-cultural aspects related to religious heritage). However, these potentials have not been fully realised due to the increase of prosperous people, the tourism area’s convenience, and management gaps. This study recommends that Gorontalo should establish a planning policy to develop a new institutional stance by regulators and the local community. Religious tourism has unique characteristics that revolve around the halal tourism industry and it’s long-term sustainability.